2012
DOI: 10.1111/j.1740-8709.2012.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

An online survey of knowledge of the weaning guidelines, advice from health visitors and other factors that influence weaning timing in UK mothers

Abstract: The UK weaning guidelines recommend the introduction of solid food at or around 6 months. The evidence suggests that knowledge of the guidelines is high, although only a small minority of parents wait until 6 months to wean. The aim of this study was to assess understanding of the UK weaning guidelines in a sample of UK parents and investigate the associations of this understanding with weaning timing, and in comparison to other influencing factors. This study conducted an online survey of UK parents. Eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 12 publications
10
68
3
1
Order By: Relevance
“…Our findings show that an accurate knowledge of the weaning guidelines, in each of these communities, is important in influencing later weaning. However, overall understanding of the guidelines was considerably lower in these BME groups, with only 56 % of respondents having an accurate knowledge and younger mothers particularly having a lower level of awareness than has been shown in our previous survey of a predominantly white population, in which 86 % of respondents had an accurate understanding (7) .…”
Section: Discussioncontrasting
confidence: 72%
“…Our findings show that an accurate knowledge of the weaning guidelines, in each of these communities, is important in influencing later weaning. However, overall understanding of the guidelines was considerably lower in these BME groups, with only 56 % of respondents having an accurate knowledge and younger mothers particularly having a lower level of awareness than has been shown in our previous survey of a predominantly white population, in which 86 % of respondents had an accurate understanding (7) .…”
Section: Discussioncontrasting
confidence: 72%
“…This contrast in when to commence complementary feeding has previously been reported to vary by country [28][29][30]. A recent online questionnaire study of 3607 mothers, suggested that those who weaned early were more focused on putative signs of readiness, whereas those weaning later were more focused on the infant reaching the recommended age.…”
Section: Discussionmentioning
confidence: 87%
“…As Table 2 outlines, most existing studies have recruited participants who self-identify as following a BLW approach [16,17,18,19,20,21], with all of the ambiguity that this entails. Only the work of Brown and colleagues [16,17,18] uses a more distinct definition to discriminate between those following a Baby-Led approach and those using more conventional feeding, by asking parents to estimate the proportion of food that is provided as purĂ©es or spoon-fed.…”
Section: What Is Baby-led Weaning and When Should It Begin?mentioning
confidence: 99%